Are recent cohorts of women with engineering bachelors less likely to stay in engineering? - Kahn, Shulamit; Ginther, Donna K. (Frontiers in Psychology, 2015)
Women are an increasing percentage of Bachelors in Engineering (BSEs) graduates – rising from 1% in 1970 to 20% in the 2000s – encouraged by increasing K-12 emphasis on attracting girls to STEM and efforts to incorporate engineering and technology into K-12 curricula. Retention of women in STEM and in engineering in particular has been a concern historically. In this paper, we investigate whether this gap has increased because a larger proportion of females entering engineering find themselves ill-matched to this field, or whether the gap has decreased as engineering becomes more accommodating to women. Using 1993 - 2010 nationally representative NSF SESTAT surveys, we compare cohorts of BSEs at the same early-career stages (from 1-2 years to 7-8 years post-bachelors). We find no evidence of a time trend in the gender gap in retention in engineering and a slightly decreasing gender gap in leaving the labor force. We find, as others have, that the majority of the gender retention gap is due to women leaving the labor force entirely and that this exit is highly correlated with child-bearing; yet women with engineering majors are half as likely as all college-educated women to leave the labor market. There are no clear time trends in female BSEs leaving the labor market. Single childless women are actually more likely than men to remain in engineering jobs. Some gender differences in retention others found are caused by differences in race and engineering subfield. With controls for these, there is no gender retention difference by 7-8 years post-bachelors for those full-time employed. There were two usual cohorts – women with 1991-1994 BSEs were particularly likely to remain in engineering and women with 1998-2001 BSEs were particularly likely to leave engineering, compared to men. Cohorts before and after these revert towards the mean, indicating no time trend. Also, women who leave engineering are just as likely as men to stay in math-intensive STEM jobs.